2018
DOI: 10.1038/s41467-018-06241-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric assembly of high-value α-functionalized organic acids using a biocatalytic chiral-group-resetting process

Abstract: The preparation of α-functionalized organic acids can be greatly simplified by adopting a protocol involving the catalytic assembly of achiral building blocks. However, the enzymatic assembly of small amino acids and aldehydes to form numerous α-functionalized organic acids is highly desired and remains a significant challenge. Herein, we report an artificially designed chiral-group-resetting biocatalytic process, which uses simple achiral glycine and aldehydes to synthesize stereodefined α-functionalized orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 47 publications
0
44
1
Order By: Relevance
“…1,4,20 Cascade biocatalysis has been developed in recent years as a promising method for the efficient synthesis of pharmaceutical intermediates and ne chemicals. [21][22][23][24] Cascade biocatalysis comprises multiple biocatalytic reactions in a single reaction vessel without the isolation of any intermediate, and starting from cheap and available substrates. 21,23,25 Because L-amino acids are mostly available through fermentation from inexpensive and renewable natural sources, multi-enzyme cascades for the biocatalytic stereoinversions of L-amino acids into Damino acids represent economically effective and environmentally benign methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,20 Cascade biocatalysis has been developed in recent years as a promising method for the efficient synthesis of pharmaceutical intermediates and ne chemicals. [21][22][23][24] Cascade biocatalysis comprises multiple biocatalytic reactions in a single reaction vessel without the isolation of any intermediate, and starting from cheap and available substrates. 21,23,25 Because L-amino acids are mostly available through fermentation from inexpensive and renewable natural sources, multi-enzyme cascades for the biocatalytic stereoinversions of L-amino acids into Damino acids represent economically effective and environmentally benign methods.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Cascade biocatalysis comprises multiple biocatalytic reactions in a single reaction vessel without the isolation of any intermediate, and starting from cheap and available substrates. 21,23,25 Because L-amino acids are mostly available through fermentation from inexpensive and renewable natural sources, multi-enzyme cascades for the biocatalytic stereoinversions of L-amino acids into Damino acids represent economically effective and environmentally benign methods. 8,[26][27][28] Herein, based on the reaction route involving L-amino acid deaminase and D-amino acid dehydrogenase, 8 we constructed and optimized the biocatalytic cascade route for the synthesis of D-amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have confirmed that artificial biocatalytic cascade is a useful tool to overcome challenging reactions. A recently reported chiral‐group‐resetting biocatalytic cascade process used simple achiral glycine and aldehydes to synthesize 45 types of α‐functionalized organic acids (Song et al, ). Similarly, three new types of asymmetric functionalizations of terminal alkenes were developed by cascade biocatalysis to produce a group of chiral ( S )‐α‐hydroxy acids, ( S )‐1,2‐amino alcohols, and ( S )‐α‐amino acids with high e.e.…”
Section: Discussionmentioning
confidence: 99%
“…The platform was designed as a modular assembly, enabling the tunable and predictable operation of the biocatalysis cascade. The modular assembly involving the basic module and the extender module has been applied to transformation of simple achiral glycine and aldehydes to synthesize stereodefined α-functionalized organic acids (Song et al 2018). This method was suitable for application as a high-yield, high-productivity platform for scaled-up HMTBA biosynthesis in a 1-L biocatalytic reaction system.…”
Section: Introductionmentioning
confidence: 99%